Elevated Levels of Circulating Biomarkers Related to Leaky Gut Syndrome and Bacterial Translocation Are Associated With Graves’ Disease - Zheng, Dekai; Liao, Huimin; Chen, Shuze; Liu, Xiuying; Mao, Chuyin; Zhang, Cangui; Meng, Min; Wang, Zhi; Wang, Ying; Jiang, Qinrui; Xue, Yaoming; Zhou, Lin; et al. (Frontiers in Endocrinology, 2021)
Background A growing number of studies have found dysbiosis of the intestinal microbiota in patients with Graves’ disease (GD). The intestinal epithelial barrier serves as the first line of defense, protecting the immune system from excessive stimulation of microbiota and toxins. Most autoimmune diseases are associated with a gut barrier dysfunction (leaky gut) which allows bacterial translocation. However, to date, potential correlations between intestinal barrier dysfunction and GD have not been explored. Methods Serum lipopolysaccharide (LPS), intestinal fatty acid-binding protein (I-FABP), zonulin, D-lactate, and diamine oxidase (DAO) were measured to assess barrier integrity in 91 patients with GD (61 initial GD and 30 euthyroid GD) and 44 healthy controls. The quality of life (QOL) of patients with GD was assessed using the thyroid-specific patient-reported outcome (ThyPRO-39) questionnaire. Results The serum levels of LPS, I-FABP, zonulin, and D-lactate were significantly higher in patients with initial GD than in healthy controls. Logistic regression analysis revealed that zonulin and D-lactate were independently associated with risk for GD and circulating zonulin could effectively distinguish patients with initial GD from healthy controls. Correlation analyses showed that I-FABP, LPS, and D-lactate were positively associated with FT4 and negatively associated with TSH. In addition, circulating LPS, zonulin, and D-lactate levels were all independent predictors of TRAb levels. Moreover, higher circulating LPS levels in patients with GD were associated with more severe hyperthyroidism (higher concentrations of FT3, FT4, and TRAb and lower TSH concentrations) and worse scores of hyperthyroid and eye symptoms. Conclusion Patients with initial GD show a disrupted intestinal barrier, characterized by elevated levels of leaky gut biomarkers. Increased intestinal permeability and bacterial translocation were associated with TRAb levels and hyperthyroidism in GD. Further research is required to elucidate the underlying mechanisms.